Trends In Ischemic Heart Disease In Indonesia From 2019–2023: A Global Burden Of Disease-Based Study with Gender Analysis (Male And Female) - Rizka Triadiati Ikhsantiningtyas Pratisti; Utami Utami; Vita Widyasari (Jurnal Kesehatan Amanah, 2026)
This study aims to analyze the trends in the prevalence of ischemic heart disease (IHD) in Indonesia from 2019 to 2023 based on data from the Global Burden of Disease (GBD) study, with a focus on gender differences between males and females. The data used in this study includes detailed prevalence data for IHD based on province and gender. The analysis reveals that the prevalence of IHD is higher in males than in females, with greater fluctuations observed in females, particularly after menopause. Although there are significant differences in the prevalence across several provinces, risk factors such as smoking, obesity, hypertension, and diabetes contribute significantly to the increasing prevalence of this disease. However, the differences in prevalence between provinces and genders are not always statistically significant, indicating that other factors such as access to healthcare, lifestyle, and socio-economic factors also influence the distribution of this disease. This study provides valuable insights for the development of gender-based heart disease prevention policies and introduces more targeted interventions.